EVALUASI STRATEGI PENETAPAN DESTINASI WISATA UNGGULAN KOTA SAMARINDA - Siti Muajimah; Emmelia Nadira Satiti; Suparwi Suparwi (LPPM Politeknik Pajajaran ICB Bandung, 2025)
This study discusses the evaluation of strategies for determining leading tourist destinations in Samarinda City as an important step in improving regional tourism competitiveness. The determination of leading tourist destinations is seen as a strategic policy that not only aims to strengthen the city's tourism identity but also encourages local economic growth through increased tourist visits, infrastructure development, and the empowerment of communities around the destinations. This study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and document studies obtained from government agencies and destination managers. Analysis is conducted inductively, emphasising the involvement of the Pentahelix elements—government, academia, business actors, communities, and media—in the entire designation process. The research findings indicate that the City Government of Samarinda designates priority destinations through a competitive selection process with systematic stages. The research findings also highlight several challenges faced, including limited operational and promotional budgets, suboptimal time management in implementing strategies, and the need to enhance the human resource capacity of destination managers. Therefore, this study recommends the development of measurable and nationally standardised technical guidelines, as well as capacity-building initiatives for managers through...